Designs for Research, Teaching and Learning A Framework for Future Education - Björklund Boistrup, Lisa; Selander, Staffan (Taylor & Francis, 2022)
This bookoffers a coherent theoretical and multimodal perspective on research, teaching and learning in different non-formal, semi-formal, and formal learning environments. Drawing on examples across a range of different settings, the book provides a conceptual framework for research on learning in different environments. It provides conceptual models around learning design which act as a framework for how to think about contemporary learning, a guideline for how to do research on learning in different sites, and a tool for innovative, collaborative design with other professionals. The book highlights concepts like multimodal knowledge representations; framing and setting; transformation, transduction, and re-design; signs of learning and cultures of recognition in different social contexts. The book supports innovative thinking on how we understand learning, and will appeal to academics, scholars and postgraduate students in the fields of education research and theory, learning sciences, and multimodal and social semiotics. It will also be of interest to school leaders, university provosts and professionals working in education.